Humble Exclusivism: Solusi Wacana Etis Otoritas Keagamaan di Ruang Digital - Muhamad Aulia Kemal Fasas (UIN Siber Syekh Nurjati Cirebon, 2025)
The digitalization of religious authority faces a moral and epistemic crisis driven by social media's algorithmic logic, which favors performative popularity over institutional knowledge. This research aims to formulate